Analisis User Experience pada Website Dinas Pemberdayaan Masyrakat dan Desa Kabupaten Sumabawa dengan Heuristic Evaluation - Husin, Husin; Balafif, Sabri; Ardianto, Efri Tri (BIOS : Jurnal Teknologi Informasi dan Rekayasa Komputer, 2024)
This research is about software usability or what is often called a usability evaluation which analyzes or tests the ease of use of the PMD (Community and Village Empowerment Service) Sumbawa Regency website. Usability is a technique for testing or measuring software applications that are considered from five aspects, namely branding, usability, functionality, and content against the ten principles of Heuristic Evaluation (HE) and System Usability Scale (SUS). Data collection in this research used the interview method with 50 respondents with 34 questions in the questionnaire, then the data was processed using validation tests and reliability tests on SPSS tools. The usability aspects tested in this research are evaluation of user experience based on visibility of system status of 86%, level of match between system and reality (match between system and the real world) of 85%, level of user control and freedom (user control and freedom) of 80%, level of consistency and standards (consistency and standards) of 84%, level of error prevention (error prevention) of 80%, level of discovery (Recognition rather than recall) of 77%, level of flexibility and efficiency of use (flexibility and efficiency of use) of 82.5%, level of aesthetic and minimalist design (aesthetic and minimalist design) of 81%, level of help users recognize, diagnose, and recover from errors (help users recognize, diagnose, and recover from errors) of 85%, level of help and documentation (help and documentation) of 80%.